PEMETAAN DAERAH RAWAN KRIMINALITAS DI KECAMATAN RAWAS ULU, KABUPATEN MURATARA, SUMATERA SELATAN - Febyani, Tiara Khofifah; Syahar, Fitriana (JURNAL BUANA, 2024)
Crime is a common problem, especially cases of robbery in Rawas Ulu District, but data on locations indicated to be prone to robbery is not yet available, so research was conducted using sig by utilizing primary data on reported cases of robbery at the Muratara Police and secondary data in the form of border shp. Sub-districts as well as location points and activity centers in the research area and nearest neighbour analysis was carried out at the point of occurrence. The nearest neighbour average results show a clustered distribution pattern of robbery incidents. The locations of the robbery incidents were in Lubuk Kemang Village, Lesung Batu Village and Karang Anyar Village, but the most frequent occurrence was in Karang Anyar Village, 18 of the 21 cases reported.